LANGUAGE DEVELOPMENT IN EARLY CHILDHOOD PERSPECTIVE A CAREER MOTHER - Anni Annisa; Uswatun Hasanah (LPPM STAI DARUSSALAM LAMPUNG, 2022)
Abstract Early childhood is person who have in a golden age (Golden age). Because at that time, early childhood had an elasticity in the right brain to learn a anguages, so that the absorption of language acquisition was easier. Language is one aspect that needs to be improved for early childhood. Early childhood language development is related to the role of a mother in their life. This study aims to find and analyze language development of early childhood in terms of mothers who have a career in Sumenep City. This research uses qualitative methods. The data collection methods used the interviews and observations. The conclusion of the study is the emotional development of children aged 5-6 years in the review of working mothers develops quite well if the mother who has a career is able to divide the roles as career women and housewives who have the obligation to educate children. There is a slight problem that the child finds, namely that not all of the child's needs can be fulfilled by the biological mother, because their mother at work, even though his presence to the child is irreplaceable. So this is where the important role of a companion mother in replacing her position as a real mother. For that it is requires special criteria for persons to be a nanny mother.